CONTENT VALIDITY OF ENGLISH SUMMATIVE TEST ITEMS OF THE EIGHTH GRADE STUDENTS AT SMPN 4 POLLUNG IN ACADEMIC YEAR 2017/2018 - Patricia Adelina Lumban Gaol; Willem Saragih; Anggraini Thesisia Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This study aimed to describe the content validity of English summative test items of the eighth grade students at SMPN 4 Pollung in connection with the learning indicators, to investigate the reason of describing content validity and to write the test items with good content validity.In this study, the researcher used descriptive qualitative design. The data in this study were the test items of summative test that obtained by coming and asking the test from the English teacher at the school. This study described the conformity and inconformity of the English summative test items in the even semester of the eighth grade students at SMPN 4 Pollung with the learning indicators. Then the researcher interpreted the conformity level of the English summative test to the learning indicators in term of content validity by using Arikunto’s criteria.The findings of this study showed that the test items is 35% conform to the learning indicators and it falls into the level 21 – 40% which is called poor. It means that the content validity of the English summative test items of the eighth grade students of SMPN 4 Pollung is poor.   Keywords: content validity, summative test.